2013
DOI: 10.1002/hep.26224
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-mediated sorafenib resistance can be overcome by EF24 through Von Hippel-Lindau tumor suppressor-dependent HIF-1α inhibition in hepatocellular carcinoma

Abstract: The increasing incidence of hepatocellular carcinoma (HCC) is of great concern not only in the United States but throughout the world. Although sorafenib, a multikinase inhibitor with antiangiogenic and antiproliferative effects, currently sets the new standard for advanced HCC, tumor response rates are usually quite low. An understanding of the underlying mechanisms for sorafenib resistance is critical if outcomes are to be improved. In this study we tested the hypothesis that hypoxia caused by the antiangiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
229
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(257 citation statements)
references
References 17 publications
5
229
0
Order By: Relevance
“…Although sorafenib downregulates the synthesis of hypoxia-inducible factor (HIF)-1α in HCC cells in vitro and in vivo [32] , the correlation of sorafenib resistance and hypoxic microenvironment is attractive because the antiangiogenic activity of sorafenib is speculated to lead to tumor starvation and subsequent tumor hypoxia [33] . A recent study [34] has shown that sorafenib-resistant HCC tissues had higher expression of HIF-1α than sorafenibsensitive and pre-treated HCC tissues. In xenograft models, the increased hypoxia because of sustained sorafenib therapy was associated with sorafenib sensitivity.…”
Section: Hypoxic Microenvironment and Sorafenib Resistancementioning
confidence: 99%
“…Although sorafenib downregulates the synthesis of hypoxia-inducible factor (HIF)-1α in HCC cells in vitro and in vivo [32] , the correlation of sorafenib resistance and hypoxic microenvironment is attractive because the antiangiogenic activity of sorafenib is speculated to lead to tumor starvation and subsequent tumor hypoxia [33] . A recent study [34] has shown that sorafenib-resistant HCC tissues had higher expression of HIF-1α than sorafenibsensitive and pre-treated HCC tissues. In xenograft models, the increased hypoxia because of sustained sorafenib therapy was associated with sorafenib sensitivity.…”
Section: Hypoxic Microenvironment and Sorafenib Resistancementioning
confidence: 99%
“…Treatments were initiated when tumors reached a mean group size of about 100 mm 3 . Tumor volume (mm 3 ) was measured with calipers and calculated as (W 2 ÂL)/2, where W is the width and L is the length.…”
Section: Measurement Of In Vivo Activitymentioning
confidence: 99%
“…Conventional radio/chemotherapies are generally not prescribed for advanced hepatocellular carcinoma due to their low efficacies (2). We and other groups (3,4) have found that the expression of HIF-1a is increased in most hepatocellular carcinomas and is associated with poor outcomes. Because fibrogenesis during the development of cirrhosis ultimately destroys the normal blood supply to the liver, the blood supply is limited in hepatocellular carcinoma with cirrhosis, which ultimately leads to local hypoxia (5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that sustained sorafenib treatment may promote hypoxia within tumors, which has been associated with sorafenib-resistance in HCC patients as well as subcutaneous mice models of HCC (10). In addition, it was reported that short-term sorafenib therapy reduced vascularization, resulting in increased tumor hypoxia (11).…”
Section: Introductionmentioning
confidence: 99%